IMPROVING MARKETING PERFORMANCE THROUGH MARKET ORIENTATION AND ENTREPRENEURIAL ORIENTATION WITH PRODUCT INNOVATION AS AN INTERVENING VARIABLE - Tengku Putri Lindung Bulan; Rahmi Meutia (Jurnal Apresiasi Ekonomi, 2025)
Langsa City is one of the cities in Aceh Province where the majority of the MSME sector is in trade. The purpose of this study is to analyze the effect of market orientation and entrepreneurial orientation on marketing performance with product innovation as an intervening variable. The population in this study was all MSME actors in Langsa City, with a sample of 97 respondents. The data analysis method uses Structural Equation Modeling, which is based on Partial Least Squares components. The results show that market orientation has a significant effect on product innovation, market orientation has no significant effect on marketing performance, entrepreneurial orientation has a significant effect on product innovation, entrepreneurial orientation has a significant effect on marketing performance, product innovation has no significant effect on marketing performance through product innovation as a variable intervening, and entrepreneurial orientation have no significant effect on marketing performance through product innovation as an intervening variable.